2011
DOI: 10.1002/cncr.26227
|View full text |Cite
|
Sign up to set email alerts
|

Associations of human leukocyte antigen class II genotypes with human papillomavirus 18 infection and cervical intraepithelial neoplasia risk

Abstract: BACKGROUND: Only a small proportion of women infected with human papillomavirus type 18 (HPV18) may progress to persistent infection and cervical neoplasia. This community-based cohort study aimed to assess associations with human leukocyte antigen (HLA) class II genotypes for natural infection of HPV18 and subsequent risk of cervical neoplasia. METHODS: Among 10,190 cytologically normal participants, 125 with HPV18 infection were identified by HPV blot kit. HPV18 viral load at study entry was examined by real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
(46 reference statements)
2
9
0
Order By: Relevance
“…We found a decreased risk of CSCC in association with the HLA-DPB1*05:01 allele and +550 G/G genotype and G allele and an increased risk in association with the +550 A allele. When the analysis was restricted to the subgroup of women with HPV-16 positive CSCC, the association of HLA-DPB1*05:01 allele still existed and the DPB1 Certain HLA class II alleles have been reported to influence cervical cancer development by affecting the interactions between host immune response and HPV infection [23][24][25][26]. The DRB1 and DQB1 loci therefore have been thoroughly investigated in several cervical cancer association studies [5].…”
Section: Discussionmentioning
confidence: 99%
“…We found a decreased risk of CSCC in association with the HLA-DPB1*05:01 allele and +550 G/G genotype and G allele and an increased risk in association with the +550 A allele. When the analysis was restricted to the subgroup of women with HPV-16 positive CSCC, the association of HLA-DPB1*05:01 allele still existed and the DPB1 Certain HLA class II alleles have been reported to influence cervical cancer development by affecting the interactions between host immune response and HPV infection [23][24][25][26]. The DRB1 and DQB1 loci therefore have been thoroughly investigated in several cervical cancer association studies [5].…”
Section: Discussionmentioning
confidence: 99%
“…Some HPV studies have reported very powerful associations. For example, a case control study for HPV by Powell et al (2011) reported ORs as high as 2770; Chen et al (2011), as high as 75; Chuang et al (2012), ORs 18.1 and higher; and Almonte et al (2011), ORs of 16.1 [46-49]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the HLA-A∗02-B∗51 haplotype was associated with resistance to disease. Susceptibility to HPV infection or cervical cancer and precancerous lesion development was associated with the HLA class II: HLA-DRB1 alleles [34, 39–51]; HLA-DQB1 alleles [34, 39, 46, 4951]; HLA-DPB1 alleles [51]; and classes I and II haplotypes [30, 34, 4042, 48, 52, 53]. Some alleles and haplotypes had a protective effect against the progression to infection and cancer [34, 3840, 43, 46, 47, 51, 54, 55].…”
Section: Discussionmentioning
confidence: 99%